Gambaran Kecerdasan Linguistik Pada Anak Usia Dini Di Tk Al-Iman Transos Benua Ratu - Oktavia, Oktavia (AT-TUFULA: Islamic Education Early Chilldhood, 2025)
Linguistic intelligence refers to the ability to organize thoughts systematically and use language effectively, such as in writing, speaking, and reading. Linguistic intelligence is closely related to verbal skills, whether written or spoken, and their rules. This study aims to understand how young children develop language skills. This research is a qualitative descriptive study. Qualitative descriptive methods involve procedures that produce descriptive data in the form of written or spoken words from people and observed behavior. The findings of the study conclude that the researcher conducted interviews with teachers and parents regarding language development. The role of teachers and parents in linguistic intelligence, both verbally and in writing, is as facilitators and motivators. They can support this development by creating opportunities to encourage children to continuously hone their linguistic abilities.